Ransomware and its future trends: A scientometric analysis - Mohanty, Kuldeep; Goswami, Veena; Qurashi, Shahazad Niwazi; Barik, Rabindra Kumar (Scientific Modelling and Research, 2024)
The research article investigates an ever-evolving knowledge mapping of ransomware using the CiteSpace Visualization tool. The foundation for this research is the body of scientific literature on ransomware that was extracted between 2013 and 2023 from the Web of Science Core Collection database. The study methodology is a five-step procedure that follows a systematic approach from data collection to bibliometric analysis using Citespace, identifying hot research topics, analyzing the results, and offering future research paths. It provides cited reference analysis, author and country cooperation networks and co-citation networks, institution collaboration networks, annual publishing patterns, and journal co-citation analysis. Using keyword co-occurrence analysis, it also provides information about hot research topics and emerging trends that pertain to ransomware. The findings identify the most influential authors, countries, and institutions that have actively contributed to ransomware research. The current study also identifies emerging trends and hot research topics, thus providing future research directions in these areas. Ransomware is a highly sophisticated type of malware that has become a dynamic threat to the cyberspace during the last ten years. Technological and IT infrastructure developments have increased the attack surface. The capability of ransomware to wreak havoc in cyberspace has made it a persistent danger. Therefore, it is essential to carry out comprehensive research using scientometric analysis to address the worldwide landscape of ransomware and provide insights into its current situation.